2011
DOI: 10.4171/jems/277
|View full text |Cite
|
Sign up to set email alerts
|

Generalized golden ratios of ternary alphabets

Abstract: Abstract. Expansions in noninteger bases often appear in number theory and probability theory, and they are closely connected to ergodic theory, measure theory and topology. For two-letter alphabets the golden ratio plays a special role: in smaller bases only trivial expansions are unique, whereas in greater bases there exist nontrivial unique expansions. In this paper we determine the corresponding critical bases for all three-letter alphabets and we establish the fractal nature of these bases in dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
(28 reference statements)
1
30
0
Order By: Relevance
“…By the above G(m) = G( m m−1 ) and we may therefore assume m ∈ (1,2]. The authors of [4] considered m ≥ 2, and their results read as follows in our setting. In Section 3, we reprove all these results, making some of the statements more explicit and simplifying several proofs.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the above G(m) = G( m m−1 ) and we may therefore assume m ∈ (1,2]. The authors of [4] considered m ≥ 2, and their results read as follows in our setting. In Section 3, we reprove all these results, making some of the statements more explicit and simplifying several proofs.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Remark 3.1. Komornik, Lai and Pedicini [4] observed that the sequences u ∈ S ∞ with the leading 0 removed are exactly the standard Sturmian sequences. However, they omitted the word "standard".…”
Section: 1 Statementsmentioning
confidence: 97%
See 1 more Smart Citation
“…By an affine transformation it suffices to consider the alphabets {0, 1, m} with m ∈ [2, ∞). Properties (i)-(viii) below have been obtained in [17] (see Theorem 1.1, the proof of Lemma 5.3 and Remark 5.12); (ix) is due to Lai [23].…”
Section: Introductionmentioning
confidence: 91%
“…Today's already classical definition of β-expansions was introduced in late 1950s [25,23] and this concept has up to now been a subject of active research, e.g. [1,3,4,5,7,8,9,10,12,18,19,20,24,26,27,28]. The world of β-expansions is much richer than that of the usual integer-base representations as is briefly illustrated on the uniqueness issue of β-expansions.…”
Section: β-Expansionsmentioning
confidence: 99%